Criminal Responsibility for Mercenaries: A Comparative Study Between Islamic Criminal Law and International Criminal Law - Brahmana, Febi Febonecci S.; Ramadani (Al-Risalah, 2025)
This study explores the issue of criminal responsibility for mercenaries, individuals who participate in armed conflicts for material gain, either through direct recruitment or as part of organized groups. The primary purpose of the research is to analyses how criminal liability for mercenary actions is conceptualized in both Islamic Criminal Law and International Criminal Law, given the complex legal challenges posed by their involvement in cross-border conflicts. The methodology employed is normative juridical with a comparative approach, analyzing relevant legal sources including the 1949 Geneva Convention Additional Protocols and primary Islamic legal texts. The study systematically compares how each legal system treats the criminal accountability of mercenaries based on their roles during conflict. The results reveal that under Islamic Criminal Law, mercenaries who engage in rebellion (bughāt) may be subject to capital punishment, as referenced in Qur’an Surah Al-Hujurat verse 9. In contrast, International Criminal Law treats mercenaries as individuals subject to the national laws of the country where the offense occurs (locus delicti), with limited recognition of mercenaries as combatants. The originality of this study lies in its comparative framing, bridging two distinct legal traditions that are rarely analyzed together in the context of modern warfare. The implications underscore the need for a more coherent and adaptive policy framework to address the transnational nature of mercenary activity and ensure equitable legal accountability across jurisdictions.